Analisis Persediaan Beras pada PT XYZ Kabupaten Ciamis - Dwiyandhana, Raditya Naufal; Nuraini, Candra; Unang, Unang; Isyanto, Agus Yuniawan (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Rice is a basic necessity that must be fulfilled by humans at all times. PT XYZ in Ciamis Regency, which partners with State-Owned Enterprises (SOEs) and also the local government of Pamarican Sub-District, has the main task of organizing quality staple food logistics and maintaining food stability. The purpose of this research is 1) to analyze the rice inventory system based on the Economic Order Quantity (EOQ) method. 2) to analyze the efficiency of PT XYZ's rice inventory costs by comparing the actual inventory costs with the effective inventory costs. The research period began from July 2023 to June 2024. The research method used a case study approach with quantitative analysis. This research was conducted at Jalan Raya Pamarican - Banjar KM 1.3 RT. 002 RW.001 Dusun Cibenda, Neglasari Village, Pamarican Sub-District, Ciamis Regency. The results showed that the rice inventory system based on the Economic Order Quantity (EOQ) method obtained a total inventory cost of Rp521.419.740,66, which means that this cost is less than the actual cost that the company must incur of Rp580.792.800. So there is a cost efficiency of Rp59.373.059,34, or 10,22% of the total inventory cost using the EOQ method.